2020
DOI: 10.1055/s-0039-3402077
|View full text |Cite
|
Sign up to set email alerts
|

The Distance between Tibial Tubercle and Trochlear Groove Correlates with Knee Articular Torsion

Abstract: This study aims to correlate the tibial tubercle to trochlear groove (TT-TG) distance with knee axial alignment. The hypothesis is that as internal torsion of the distal femur or external torsion of the proximal tibial increases, the TT-TG distance increases. We designed a cross-sectional study approved by our institutional ethics review board. We reviewed 32 computed tomography angiographies of patients that have nonjoint or bone-related symptoms. Distal femoral torsion, proximal tibial torsion, knee articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…TT-TG has been previously used to evaluate patellofemoral instability, and subsequent studies have revealed that the TT-TG distance is significantly greater in patients with non-contact ACL injury than in normal knees and correlates with knee torsion, which is considered a similar axial measurement parameter [ 15 , 17 , 27 ]. Usually, a larger TT-TG indicates greater external rotation of the tibia relative to the femur and greater stress on the ACL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TT-TG has been previously used to evaluate patellofemoral instability, and subsequent studies have revealed that the TT-TG distance is significantly greater in patients with non-contact ACL injury than in normal knees and correlates with knee torsion, which is considered a similar axial measurement parameter [ 15 , 17 , 27 ]. Usually, a larger TT-TG indicates greater external rotation of the tibia relative to the femur and greater stress on the ACL.…”
Section: Discussionmentioning
confidence: 99%
“…Alpay et al identified femoral anteversion leading to abnormal torsion of the infratrochanteric femur as a risk factor for ACL injury [ 14 ]. The tibial tubercle to trochlear groove (TT-TG) distance, an indicator of knee torsion, is an essential factor in non-contact ACL injury, and a larger TT-TG increases tibial internal rotation, exposing the ACL to greater tension, thus increasing the risk of injury [ 15 17 ]. Non-contact ACL injury is usually due to a pivot-shift mechanism resulting from the combined action of the femur and tibia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The technique which the MRI scans were conducted was not uniform, as it was performed by different operators and MRI machines, producing MRI scans with variable quality, which may affect the readers’ measurements [1, 17]. Another possible limitation of the study could be attributed to the difference in TTTG distances measured on MRI and CT, affecting the values of pathologic cutoffs [3, 8, 10, 33]. However, it seems that the measurement technique employed, when evaluating the TTTG distance, plays a major role in regard to modality inter‐rater agreement as was shown by Camp et al [5].…”
Section: Discussionmentioning
confidence: 99%
“…There was no information available on the exact TTO technique that was used for primary surgery as well as no data were given on TT-TG and TT-PCL distances prior to first TTO, which can be considered as crucial for determining the amount of required intraoperative tibial tubercle medialization [ 30 , 31 ]. However, a high TT-TG distance alone does not automatically mean that TTO is the treatment of choice, given the multitude of factors influencing TT-TG measurement and distance, including trochlea dysplasia and femoral antetorsion [ 32 , 33 ]. Although RL-TTO showed encouraging results, severe cartilage damage in the medial part of the patellofemoral joint during revision surgery was striking in this young patient cohort.…”
Section: Discussionmentioning
confidence: 99%